Assessing Procedural Justice in the Administration of Small-Scale Benthic Fisheries in Chile - Estévez, Rodrigo A.; Jerez, Gabriel; Gelcich, Stefan (Frontiers in Marine Science, 2021)
In order to navigate toward ocean sustainability, policies, programs, and scientific research must address issues of justice. In fisheries management, justice has generally been understood in terms of the distribution of social, cultural, and economic benefits. However, there are also important procedural justice challenges in the fisheries system, which are fundamental to the long-term sustainability and equity of the oceans. Procedural justice is related to the conditions under which the negotiation for benefit distribution takes place. That is, the procedures, structures, and processes that lead to the distribution of resources. In this study, we empirically assess fishers’ perceptions of procedural justice components within a small-scale fishery management policy in Chile which has been shifting toward a polycentric type of governance during the past 7 years. We specifically assess perceptions of management committee members. Management committees have been constituted as spaces of collective action for participatory decision-making. We decompose procedural justice in seven subcomponents and assess perceptions associated to achievement in the administration of fisheries. Our results show that management committee members perceive heterogeneity in the achievement of different procedural justice components, which is a central element in achieving equitable development in the oceans. The highest perceptions of achievement were found in the procedures for the selection of participants, the use of various types of technical and local knowledge for decision-making, and the perception by participants of ethical and impartial procedures. We also identified significant challenges related to an inflexible legal structure that hinders adaptive management and learning as a tool for institutional transformation. In addition, mechanisms for communicating decisions to users and clear accountability procedures were perceived as weak. It is critical to address these gaps as they can jeopardize the implementation and legitimacy of fisheries management. Focusing on different components of procedural justice can provide an important lens through which advances and gaps in fisheries policy can be identified and worked upon.